KI HADJAR DEWANTARA'S MORAL VALUES AND CONTEMPORARY CHARACTER EDUCATION: A QUALITATIVE LITERATURE REVIEW - Dheria Febriana Putri; Devia ambarista; Dian Asri Ratna Juni; Fera Febriyanti; Fina Zakiyah; Fikka Maypalita; Eggie Nugraha (Politeknik Penerbangan Surabaya, 2025)
Character education remains central to educational reform, yet prior discussions of Ki Hadjar Dewantara often restate his ideas without critically connecting them to contemporary moral education. This qualitative literature review examines the relevance of Dewantara's concept of budi pekerti to current character education. Literature was identified through Google Scholar, ERIC, DOAJ, and publisher databases using Indonesian and English keywords related to Ki Hadjar Dewantara, moral education, values education, character education, digital citizenship, and multicultural education. The review covered peer-reviewed publications from 2019–2025 and included Dewantara's foundational educational work. Sources were selected for conceptual relevance, methodological clarity, and contribution to educational practice. Fifteen substantive sources were synthesized through reflexive thematic analysis. Four themes emerged: integrated moral development through thought, feeling, will, and action; moral formation through example, habituation, dialogue, and learner agency; the Tri-Center partnership among family, school, and community; and the extension of budi pekerti to digital citizenship, multicultural inclusion, and twenty-first-century competencies. The review's novelty lies in interpreting Dewantara's philosophy as a dynamic framework that combines local moral foundations with critical, democratic, and digitally responsible character education. Practically, the findings support curriculum integration, teacher modelling, participatory learning, and coordinated school-family-community programmes. The review concludes that Dewantara's philosophy remains relevant when implemented reflectively rather than as moral indoctrination.